2022
DOI: 10.3389/fmars.2022.758013
|View full text |Cite
|
Sign up to set email alerts
|

Marine Mammal Interactions With Fisheries: Review of Research and Management Trends Across Commercial and Small-Scale Fisheries

Abstract: Marine mammal interactions with fisheries, such as bycatch and depredation, are a common occurrence across commercial and small-scale fisheries. We conducted a systematic review to assess the management responses to marine mammal interactions with fisheries. We analyzed literature between 1995 and 2021 to measure research trends in studies on direct and indirect interactions for: (i) high and low to middle-income countries, (ii) fishery operations (commercial and small-scale), and (iii) taxonomic groups. Manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 164 publications
(223 reference statements)
0
19
0
Order By: Relevance
“…Valencia fishers are still very collaborative with conservation workers and aware of conservation issues; however, management actions are needed for both keeping the fishing activity sustainable and preserving the dolphin populations in the area. Future work must focus on updating extant knowledge in cetacean species abundance, distribution, behavior, and habitat use in order to assess spatial risk (Jog et al, 2022), but it is also necessary to implement management actions for reducing cetacean-fisheries interactions, such as the use of visual deterrent devices, acoustic deterrent devices, and gear modifications, also contributing with compensation funds to fishers in order to reduce these interactions (Jog et al, 2022). participated in the interviews.…”
Section: Combination Of Methodologies and Future Management Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Valencia fishers are still very collaborative with conservation workers and aware of conservation issues; however, management actions are needed for both keeping the fishing activity sustainable and preserving the dolphin populations in the area. Future work must focus on updating extant knowledge in cetacean species abundance, distribution, behavior, and habitat use in order to assess spatial risk (Jog et al, 2022), but it is also necessary to implement management actions for reducing cetacean-fisheries interactions, such as the use of visual deterrent devices, acoustic deterrent devices, and gear modifications, also contributing with compensation funds to fishers in order to reduce these interactions (Jog et al, 2022). participated in the interviews.…”
Section: Combination Of Methodologies and Future Management Actionsmentioning
confidence: 99%
“…The opposite situation seems to happen at Valencia province, where low engine power contribution values do not explain the clusters of striped dolphin strandings, probably associated with the proximity to the preferred area of distribution for striped dolphin in the region. Therefore, fishing capacity alone does not seem to explain the stranding distribution throughout the region The effect of other variables such as species distribution (Leeney et al, 2008), abundance of cetacean species and/or of their prey, or drifting conditions and migration of carcasses due to sea currents and winds (Peltier et al, 2014;Saavedra et al, 2017;Jog et al, 2022) should be also considered to explain cetacean distribution. In fact, at the study area, the stranding clusters of both dolphin species found at the south of the Valencia province could be explained by the existence of a main north-south surface coastal current, already described as a potential factor explaining loggerhead sea turtle stranding distribution in the area (Tomaś et al, 2008).…”
Section: Assessment Of Fisheries Interactions According To Strandingsmentioning
confidence: 99%
“…Expansion of human populations and local fisheries have led to increasing opportunities for competition with coastal marine predators. A recen review by Jog et al (2022) shows that the number of published studies of marine mammal interactions with fisheries is rising and is largely dominated by cetaceans in both commercial and small-scale fisheries. Depredation of catches in at least 214 fisheries covering almost all of FAO's (Food and Agriculture Administration) fishing areas has been reported since 1979 (Northridge, 1991;Tixier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Depredation of catches in at least 214 fisheries covering almost all of FAO's (Food and Agriculture Administration) fishing areas has been reported since 1979 (Northridge, 1991;Tixier et al, 2020). Marine mammals such as cetaceans and pinnipeds are the most frequently reported taxonomic groups that exhibit this behavior (Tixier et al, 2020;Jog et al, 2022). Depredation of small-scale fisheries is less frequently reported for pinnipeds due to the distributions of this type of fisheries; within the odontocetes, killer whales (Orcinus orca) and common bottlenose dolphins (Tursiops truncatus, hereafter referred to as "bottlenose dolphin"), possess the highest number of depredation reports, but only bottlenose dolphin has been documented to interact with different types of fishing gear used by the recreational, commercial, and artisanal sectors (Northridge, 1984;Tixier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation